Insights on value-based healthcare implementation from Dutch heart care. (2nd July 2020) - van der Nat, P. B.; van Veghel, D.; Daeter, E.; Crijns, H. J.; Koolen, J.; Houterman, S.; Soliman, M. A.; de Mol, B. A.; ,
ABSTRACT: Value-based healthcare has been introduced in 2006. Ten years later, this concept is adopted by a growing number of healthcare organizations. However, little is known about the practical implementation of value-based healthcare within hospitals. While working on the implementation of value-based healthcare in Dutch heart care, physicians are confronted with three main challenges that still need to be addressed to make value-based healthcare successful. First, it will require a shift in our thinking to actually use outcomes as drivers for quality improvement instead of as end points in scientific studies. Secondly, it will require tools for linking outcomes to quality of care processes enabling quicker and continuous improvement cycles. Finally, platforms are needed where benchmarking on outcomes is connected to an open learning and sharing environment where physicians can discuss good care delivery practices.